2018
DOI: 10.18203/2320-1770.ijrcog20185406
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality related to postpartum hemorrhage: a case-control study at the Befelatanana maternity of Madagascar

Abstract: Background: Postpartum hemorrhage (PPH) remains the main cause of maternal death throughout the world. present goal was to determine the associated factors to maternal death in postpartum hemorrhage.Methods: This was a retrospective case-control study; carried out within Befelatanana maternity, in Antananarivo, from January 1st, 2013 to December 31st, 2015, on parturients who presented PPH. The cases were represented by the parturients who died despite well-managed care, and the control, by the living parturie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…Our study is in concordance 16,10 but the study conducted showed otherwise. 11 We did not fi nd any signifi cant association 68 Omari, Yusrawati and Yenny Indones J Obstet Gynecol between the birth attendant and maternal deaths due to hemorrhage. The present study found almost all deliveries of dead women who were already in high-risk pregnancy and severe conditions assisted by healthcare workers.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…Our study is in concordance 16,10 but the study conducted showed otherwise. 11 We did not fi nd any signifi cant association 68 Omari, Yusrawati and Yenny Indones J Obstet Gynecol between the birth attendant and maternal deaths due to hemorrhage. The present study found almost all deliveries of dead women who were already in high-risk pregnancy and severe conditions assisted by healthcare workers.…”
Section: Discussionmentioning
confidence: 59%
“…This fi nding is in line with a study in Madagascar and Turkey that showed 70.2% and 50.68% of all deaths due to haemorrhage were caused by uterine atony, respectively. 10,11 However, previous studies have shown varying results. In North-East India, uterine atony only occurs in around 15.98% of females.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations